PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK DIGITAL GUNA MENINGKATKAN KESADARAN DAMPAK BULLYING TERHADAP SELF ESTEEM SISWA TINGKAT SEKOLAH DASAR - Cahyaningtias, Oktavia Annisa; Darma, Widia; Rispatiningsih, Dwi Maryani (Dharmas Education Journal (DE_Journal), 2024)
One of the big mistakes in the character formation process is assuming that character formation must be taught in formal educational institutions. As a result, people outside formal educational institutions tend not to care or do not want to support the formation of this character. There are many events that shouldn't happen at school, starting from making fun of friends, clapping, calling friends by their parents' names, not being chosen when forming groups, not being invited to play or go to the canteen together, isolating, inciting, intimidation, oppression, no one is even willing to sit at the same table with the victim. The likelihood of bullying actually occurring depends on many factors including the psychological state of the bully, possible support or cooperation from other group members, and the victim's reaction. As technology develops, comics are starting to innovate, from initially being in physical book form to digital form. Using digital comics as a learning medium is one learning innovation that can be implemented. Digital comics can be a combination of text, images and learning videos that provide audio and visual simulations that increase students' enthusiasm for learning. The use of this learning media can change the learning process in the classroom. Development of Comic-Based Learning Media to Increase Awareness of the Impact of Bullying on Self Esteem using research and development methods. Research and development is a research method used to produce certain products and test the effectiveness of these products. In this research, the product that will be produced is a digital comic entitled "bullying doesn't make you cool" to increase awareness of the impact of bullying on elementary school students' self-esteem. The digital comic-based learning media that was developed was implemented with 64 class IV students. The initial field trial, the subjects numbering 25 students from Kanisius Wonogiri Elementary School, showed a feasibility percentage result for digital comic-based learning media of 91.2%, including the very feasible category and an effectiveness result of 0.78, including the high category. A large-scale field test with 39 students from the Unggulan Nawa Kartika Islamic Elementary School showed that the results of the feasibility percentage for digital comic-based learning media were 93%, and the effectiveness results were 0.953 indicating the high category. This research concludes that the development of digital comic-based learning media is an effective approach to increasing awareness of the impact of bullying on elementary school students' self-esteem. Through the use of digital comics, students can more easily understand complex concepts regarding bullying and its impact on self-esteem. This is reflected in students' positive responses to the use of this media in learning. The research results also show that the use of digital comics can increase students' information retention. Through the visual and narrative experiences presented in comics, students tend to remember the information provided more easily. This can help them to better understand and internalize concepts related to bullying and self-esteem.